Estendendo a NCL para promover interatividade vocal em aplicações Ginga - Carvalho, Lucas; Macedo, Hendrik (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
Vocal access to TVDi content can promote social and digital inclusion. Actually, vocal interface enhances accessibility since it enables TVDi usage by physical-impaired people and blind community. In the scientific literature, however, TVDi voice-driven interactivity is not often considered. There are just few works concerning architecture proposals, but none of them is actually properly validated. We consider the integration of VoiceXML voice gateways and the middleware Ginga a promising hypothesis for architecture definition. In this paper, we describe such an integration proposal and perform validation by means of two different case studies, two different TVDi applications. The proposal key element is the syntax extension we provide to NCL in order to incorporate some native VoiceXML elements. Results show that the vocal interactivity mechanism has achieved similar functionality to that of the remote control.